Watershed phenomena during extracorporeal life support and their clinical impact: a systematic in vitro investigation. (12th June 2020) - Gehron, Johannes; Schuster, Maximilian; Rindler, Florian; Bongert, Markus; Böning, Andreas; Krombach, Gabriele; Fiebich, Martin; Grieshaber, Philippe; ,
Abstract: Aims: Extracorporeal life support (ECLS) during acute cardiac failure restores haemodynamic stability and provides life‐saving cardiopulmonary support. Unfortunately, all common cannulation strategies and remaining pulmonary blood flow increase left‐ventricular afterload and may favour pulmonary congestion. The resulting disturbed pulmonary gas exchange and a residual left‐ventricular action can contribute to an inhomogeneous distribution of oxygenated blood into end organs. These complex flow interactions between native and artificial circulation cannot be investigated at the bedside: only an in vitro simulation can reveal the underlying activities. Using an in vitro mock circulation loop, we systematically investigated the impact of heart failure, extracorporeal support, and cannulation routes on the formation of flow phenomena and flow distribution in the arterial tree. Methods and results: The mock circulation loop consisted of two flexible life‐sized vascular models (aorta and vena cava) driven by two paracorporeal assist devices, resistance elements, and compliance reservoirs to mimic the circulatory system. Several large‐bore antegrade and retrograde access ports allowed connection to an ECLS system for extracorporeal support. With four degrees of extracorporeal support—that for cardiac failure, early recovery, late recovery, and weaning—we investigated aortic blood flow velocity, blood flow, and mixing zones using colour‐coded Doppler ultrasound in the aorta and its corresponding branches. Full retrograde extracorporeal support (3–4 L/min) perfused major portions of the aorta but did not reach the supra‐aortic branches and ascending aorta, resulting in an area in the thoracic aorta demonstrating nearly stagnant blood flow velocities during cardiogenic shock and early recovery (0 ± 4 cm/s; −10 ± 15 cm/s, respectively) confined by two watersheds at the aortic isthmus and renal artery origin. Even increased ECLS flow was unable to shift the watershed towards the aortic arch. Antegrade support resulted in homogeneous flow distribution during all stages of cardiac failure but created a markedly negative flow vector in the ascending aorta during cardiogenic shock and early recovery with increased afterload. Conclusions: Our systematic fluid‐mechanical analysis confirms the clinical assumption that despite restoring haemodynamic stability, extracorporeal support generates an inhomogeneous distribution of oxygenated blood with an inadequate supply to end organs and increased left‐ventricular afterload with absent ventricular unloading. End‐organ supply may be monitored by near‐infrared spectroscopy, but an obviously non‐controllable watershed emphasizes the need for additional measures: pre‐pulmonary oxygenation with a veno‐arterial‐venous ECLS configuration can allow a transpulmonary passage of oxygenated blood, providing improved end‐organ supply.